14 Rolling out human factors training to community support staff within the south west. (17th November 2016) - McGuinness, R; Howe, A; Durdin, C; Gleave, K; Delaney, N
Abstract : Background: Although an appreciation of the principles of Human Factors has been implemented in acute care services in recent years, training packages and resources are less applicable to the community health and social care context. Following a successful pilot, where core training was based on how teams communicate and use tools such as SBAR, support staff were enabled to help create and work in environments that optimise their ability to deliver safe, quality, patient care. The evidence also suggested that team-training to implement effective teamwork may offer the greatest impact on patient outcomes (Weaver et al, 2014). Methodology: A training package with community specific resources was developed by the pilot organisation and an acute hospital trust to reflect realistic scenarios. It was based on how teams communicate and use tools such as SBAR to develop a baseline awareness, which is built upon and embedded during the training using different scenarios. Results: In total, 385 staff received training through induction by the end of 2015, in addition to the 50 staff who received training in the first pilot phase. The target for further spread is to train an additional 2, 500 staff across 4 further community organisations in 18 months along with 45 facilitators to build a faculty of staff trained in human factors to promote safer patient care. Conclusion: Developing community specific resources, scenarios and educational packages enables the human factors message to spread beyond the acute sector, to primary care. Initial feedback from both healthcare workers and patients shows an improved team approach with clear communication. The collaboration between primary and secondary care has allowed for shared learning from previous strategies to embed human factors in healthcare. The next step will be to explore simulation to further reinforce the human factors message. Reference: Weaver S, Dy S, Rosen M. (2014) Team-training in healthcare: a narrative synthesis of the literature. BMJ Quality and Safety Online . Available online at http://qualitysafety.bmj.com/content/early/2014/02/05/bmjqs-2013-001848.full